2020
DOI: 10.1038/s41559-020-1178-6
|View full text |Cite
|
Sign up to set email alerts
|

Academic ecosystems must evolve to support a sustainable postdoc workforce

Abstract: The postdoctoral workforce comprises a growing proportion of the STEM community and plays a vital role in advancing science. Postdoc professional development, however, remains rooted in outdated realities. We propose enhancements to postdoc-centred policies and practices to better align this career stage with contemporary job markets and work life. By facilitating productivity, wellness, and career advancement, the proposed changes will benefit all stakeholders in postdoc success -including research teams, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…Several studies using mathematical modeling of COVID-19 and other coronavirus transmission have suggested that measures such as social distancing and city lockdown may be effective methods of disease control [5,6], but these seldom assess individual transmission chains. Lu et al recently sequenced SARS-CoV-2 genomes from 53 patients in Guangdong, the province of China that reported the highest number of cases (n = 1388) outside Hubei [7]. Phylogenetic analysis of these and other genomes of SARS-CoV-2 worldwide revealed that the Guangdong virus strains are scattered among strains from other Chinese provinces and other countries, consistent with the epidemiological finding that the majority of infections detected in Guangdong were imported cases.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…Several studies using mathematical modeling of COVID-19 and other coronavirus transmission have suggested that measures such as social distancing and city lockdown may be effective methods of disease control [5,6], but these seldom assess individual transmission chains. Lu et al recently sequenced SARS-CoV-2 genomes from 53 patients in Guangdong, the province of China that reported the highest number of cases (n = 1388) outside Hubei [7]. Phylogenetic analysis of these and other genomes of SARS-CoV-2 worldwide revealed that the Guangdong virus strains are scattered among strains from other Chinese provinces and other countries, consistent with the epidemiological finding that the majority of infections detected in Guangdong were imported cases.…”
mentioning
confidence: 68%
“…Thus, a lull in hiring can have disastrous consequences for these early career scientists. Postdocs are generally not as well paid as their peers outside of academia, and often lack benefits and safety nets that faculty, students, and permanent staff have access to, such as paid family leave [6,7]. This is further conflated by the fact that many postdocs are at the stage of their lives when they start families (e.g., the two-body problem) [8].…”
mentioning
confidence: 99%
See 3 more Smart Citations